Ecotoxicological effect of potassium chloride on the californian red worm (Eisenia foetida) - Ramírez Caján, Alfonso (2021)
This research presents the methodology for the evaluation of the ecotoxicological effects of potassium chloride in the red worm Eisenia foetida, through a 14-day chronic exposure bioassay. The biological material in adult stage from the worm hatchery area of ​​the Universidad Nacional Agraria La Molina, was subjected to 5 concentrations to determine the LC50 and mortality as the end point, showing deformation, discoloration, inflammation, and abnormal bulging in the clitellar zone of the worms during the process, also carrying out the measurement of the environmental parameters of pH, temperature, and humidity of the substrate (soil) at 1, 4, 7, 10 and 14 days.